PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA DAN DI DUNIA - Sindy Wahyu Silvia; Saqif Bagas Baihaqi (EKSYA : Jurnal Ekonomi Syariah, 2025)
The development of the global financial system has facilitated the emergence of Islamic banking as an alternative financial system grounded in the principles of justice and Islamic ethics. Islamic banking operates in accordance with the Qur’an and Sunnah by prohibiting practices involving riba (interest), gharar (uncertainty), and maysir (gambling). This article aims to examine the development of Islamic banking in Indonesia and globally, as well as to analyze the role of Sharia contracts in banking operations. This study employs a qualitative approach, utilizing a literature review to examine various relevant sources. The findings indicate that Islamic banking has experienced significant growth, supported by strong regulatory frameworks and increasing public awareness. The implementation of Sharia contracts is a key factor in maintaining the stability and sustainability of Islamic banking at both national and global levels.